FTIR Product Distribution Study of the Cl and OH Initiated Degradation of Methyl Acrylate at Atmospheric Pressure - Blanco, Maria Belen (2010)
A product study is reported on the gas-phase reactions of OH radicals and Cl atoms with methyl acrylate. The experiments were performed in a 1080-L quartz-glass chamber in synthetic air at 298 ( 2 K and 760 ( 10 Torr using long-path in situ FTIR spectroscopy for the analysis of the reactants and products. In the absence of NOx the major product observed in the OH reaction is methyl glyoxylate, with formaldehyde as a coproduct. For the reaction with Cl only formyl chloride (HC(O)Cl), CO, and HCl could be positively identified as products, however, the concentration-time behavior of these products show that they are secondary products and originate from the further oxidation of a major primary product. From this behavior and a comparison with simulated spectra unidentified bands in the residual product spectra are tentatively attributed to a compound of structure CH2ClC(O)C(O)OCH3, i.e., formation of methyl 3-chloro-2-oxopropanoate from the reaction of Cl with methyl acrylate. The present results are compared with previous results where available and simple atmospheric degradation mechanisms are postulated to explain the formation of the observed products.